The Small GTPase RhoA Is Required to Maintain Spinal Cord Neuroepithelium Organization and the Neural Stem Cell Pool - Herzog, Dominik (J Neurosci, 2011)
The regulation of adherens junctions (AJs) is critical for multiple events during CNS development, including the formation and maintenance of the neuroepithelium. We have addressed the role of the small GTPase RhoA in the developing mouse nervous system using tissue-specific conditional gene ablation. We show that, in the spinal cord neuroepithelium, RhoA is essential to localize N-cadherin and β-catenin to AJs and maintain apical–basal polarity of neural progenitor cells. Ablation of RhoA caused the loss of AJs and severe abnormalities in the organization of cells within the neuroepithelium, including decreased neuroepithelial cell proliferation and premature cell-cycle exit, reduction of the neural stem cell pool size, and the infiltration of neuroepithelial cells into the lumen of the ventricle. We also show that, in the absence of RhoA, its effector, mammalian diaphanous-related formin1 (mDia1), does not localize to apical AJs in which it likely stabilizes intracellular adhesion by promoting local actin polymerization and microtubule organization. Furthermore, expressing a dominant-negative form of mDia1 in neural stem/progenitor cells results in a similar phenotype compared with that of the RhoA conditional knock-out, namely the loss of AJs and apical polarity. Together, our data show that RhoA signaling is necessary for AJ regulation and for the maintenance of mammalian neuroepithelium organization preventing precocious cell-cycle exit and differentiation.